Do We Need A Quality Assessment for Note-Taking Technologies in Technology-Assisted Interpreting? A Descriptive Study - Nugrahani, Dyah -; Purnomo, SF Luthfie Arguby (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
Technology-assisted interpreting (TAI) signifies a binary concern encompassing not only the interpreting process but also the technology used. One of the technologies playing crucial roles in signifying the quality of interpreting is note-taking technology. Thereby we argue that note-taking technologies used in TAI require a specific quality assessment since they influence the process and result of interpreting. We propose a conceptual framework for a quality assessment specifically designed for note-taking technologies used in TAI by taking Aarseth’s textonomy theory (1997), Costa, Pastor, and Muňes’s technology aid based interpreting classification theory (2014), O’Brien and Toms’s user engagement theory (2008), Venkatesh and Davis’s technology acceptance model (2000), and Friedman’s immersion theory (2014). We propose that the note-taking technology quality assessment has to address three primary considerations. They are functional parameters, user’s function considerations, and interpreting types. Functional parameters, which assess the interaction between users and note-taking technologies, consist of engagement, acceptance, and immersion. User’s functions, comprising of interpretive, explorative, and configurative functions, assist the assessors in comprehending the characteristics of particular note-taking technologies. Interpreting types, classified based on the technology dominantly used in the interpreting process, helps the assessors indicate which technology fits what interpreting types.